Out with Gun and Camera; or, The Boy Hunters in the Mountains - Stratemeyer, Edward, 1862-1930 (Salt Lake City, UT : Project Gutenberg, 2004)
"Out with Gun and Camera; or, The Boy Hunters in the Mountains" by Captain Ralph Bonehill is a novel likely written in the early 20th century. The story follows a group of four boys$1 (BSheppard Reed, Frank Dawson (known as Whopper), Charley Dodge (Snap), and Will Caslette (Giant)$1 (Bwho embark on an adventurous camping trip in the mountains filled with hunting, fishing, and photography. The narrative promises to explore themes of friendship, challenges from rivals, and the joys of exploring nature. The opening of the story introduces the main characters as they plan their outing, touching on their previous adventures and current excitement. The boys are eager to pursue a summer of fun but are interrupted by a confrontation with Ham Spink and his friends, foreshadowing rivalry and challenges ahead. The narrative swiftly sets up the dynamics of friendship among the boys as they prepare for another adventure, discussing their plans and teasing each other about their abilities. Their interactions establish a lively camaraderie that promises to drive the story forward as they delve into the mountains with high spirits and great expectations. (This is an automatically generated summary.)s
Release date is 2004-07-19
Produced by Jim Ludwig
Keywords: Fishing -- Juvenile fiction; Hunting -- Juvenile fiction; Photography -- Juvenile fiction